Concentrations of lead copper and zinc in the bottom sediments of Tuba island waters of Langkawi, Malaysia - Yunus, Kamaruzzaman; Muhamad Tajudin, Nur Shuhada; Md Suhaimi, Mohd Zahir; John, Akbar; Saad, Shahbudin; Khan Chowdhury, Ahmed Jalal; Goddard, J Stephen (Oriental Scientific Publishing Co., 2011)
Surface sediments were collected from Pulau Tuba (9 sampling points) has been analyzed for Pb, Cu and Zn by using the sensitive Inductively Coupled Plasma Mass Spectrometer (ICP-MS). In this study, the average concentration of Pb, Cu and Zn were 43.28±8.95 μg.g-1 dry weights, 8.79±2.72 μg.g-1 dry weights and 63.5 μg.g-1 dry weights, respectively. In this study, the statistical analysis for Pearson correlation matrix has proved that there are significant relationship between the metal concentration and the grain size. The concentration of Pb, Cu and Zn increased with the decreased of mean size particles, suggest that there are association with the fine fraction of the sediments. In order to assess the influence of heavy metals pollution precisely, enrichment factor (EF) were calculated. In this study, all elements are about unity and considered to be dominantly terrigenous in origin.